For land and culture the grassroots council movement of Turkmens in Iran, 1979-1980 - Vahabzadeh, Peyman 1961- (Fernwood Publishing, 2024)
"For Land and Culture offers the first comprehensive account of a long forgotten and neglected grassroots movement. In the wake of Iran's 1979 revolution, Turkmen peasants collectively occupied their ancestral lands, which had been seized through colonial modernization, land registry and land reform under the Pahlavi monarchy. The book chronicles this movement using theoretical and historical engagement with the modern councils and offers a detailed account of the "land question" in Iran's colonial modernization. The book describes the systematic dispossession of Turkmen communities from some of the most fertile areas in Iran. Vahabzadeh shows how Turkmen land occupation in 1979 led to a sophisticated council system that offered a practical politics of semi-autonomous, democratic self-governance in the face of hostile militias and other forces of the nascent authoritarian Islamic Republic. With social justice as one of its unshakable pillars, the Turkmen council movement took back land as commons and abolished capitalist private ownership of land, providing an alternative to top-down politics until it was defeated by the state through a combination of military terror and assimilation. Although short lived, the radically democratic movement connected with global struggles of Indigenous Peoples and autonomous movements that had broken away from patriarchal state forms and capitalist domination."--Page 4 of cover